An effective short duration postoperative catheterization after vaginal hysterectomy and pelvic floor repair - Pant, P.R. (Journal of Institute of Medicine Nepal, 2007)
Background: The most common postoperative problem in the female bladder is atony caused by overdistention and reluctance of the patient to initiate the voluntary phase of voiding. After anterior colporraphy, spasm, edema and tenderness of the pubo-coccygeal muscles may obstruct the process of voiding. For spontaneous voiding to occur, the para sympathetic function of the bladder detrusor must be coordinated with the voluntary motor function of the abdominal wall and elevator muscles. In the past it was customary to insert an indwelling urethral catheter for 5 or more days after vaginal hysterectomy and pelvic floor repair but infect in uncomplicated cases 12- 24 hours post operative bladder catheterization is sufficient. Objective: to study the urinary symptoms, like retention of urine and frequency of micturition, in patients with short duration postoperative catheterization after vaginal hysterectomy and pelvic floor repair. Study design: This is descriptive study, comprised of 257 women, who underwent vaginal hysterectomy and pelvic floor repair under spinal anaesthesia in different districts of Nepal. They were catheterized for 12 to 24 hours and after removal of catheter urinary problems were studied. Results: Despite of different age, different degree of prolepses, different degree of cystocele and different duration of prolepses out of 257 patients only 8 patients developed urinary symptoms including retention of urine in 5 patients and frequency and burning maturation in 3 patients. They were catheterized for 12 to 24 hours. One of the patients who had retention required 5 days catheterization, while other 4 were re catheterized for 24 more hours. In all the cases there was urinary tract infection. Conclusion: Long duration postoperative catheterization 48 to 72 hours is not necessary in patients after uncomplicated vaginal hysterectomy and pelvic floor repair as practiced in many gynecological centers. Age of the patients, degree of uterine prolapse, cystocele, and duration of prolapse do not play major role in development of post catheter removal urinary symptoms. Preexisting or postoperative urinary tract infections have main role in the development of these symptoms. Journal of Institute of Medicine Vol.28(1) 2006